Electrical machines in automotive: evaluation of current technologies and future requirements - Alani, Mahir; Oner, Yasemin; Tameemi, Ahmed (SPRINGER, 2023)
This paper presents an evaluation of the current technologies and future requirements of electrical machine in automotive. First, a comparative of ten different electrical machines based on the market available electrical vehicles and hybrid electrical vehicles is made. The aim of the comparison is to evaluate the different electrical machine topologies, structure, operation conditions, and performance. The future design requirements of electrical machine in automotive are presented and several state-of-art electrical machine design techniques have been explored and studied by employing them in the compared ten machines. The conclusion of this work shows that permanent magnet topologies have the highest performance among the different electrical machine topologies and have the potential to meet the future requirements. In addition, aggressive cooling methods, i.e., spray, dripping, semi- or fully flooded, are needed to allow electrical machines to operate with the required power density target. Finally, the design to recycle concept shows the potential to be implemented in future electrical machines with little or no sacrifice of the performance.
Keywords: Electrical machine; Automotive; Electric vehicle; Electric car; PARTICLE SWARM OPTIMIZATION; PERMANENT-MAGNET MACHINES; DESIGN; ALGORITHM; Engineering